Sonic Ecosystems and Natural Cycles: An Immersive Multimedia Improvisation - Jorge E Variego (Journal of the Association for Technology in Music Instruction, 2026)
This proposal presents a 20-minute free improvisation based on the concept of natural cycles, performed by a student-led electroacoustic ensemble. The multimedia improvisation explores the ensemble as a creative sonic ecosystem where sounds emerge, dissipate, and reconstruct in altered forms, mimicking natural processes like growth, decay, and regeneration. This performance proposal is deeply rooted in the collaboration between Brian Eno and John Hassel in Possible Musics, where acoustic and electronic elements interweave, creating music that is simultaneously otherworldly and rooted in global sonic traditions. As Brian Eno noted, “Music is a process, not a thing.” This performance proposal situates music as an evolving network.
Keywords: improvisation; composition; performace